Analisi manajemen pengetahuan terhadap kepatuhan minum obat pada pasien hipertensi di apotek Medan central care pharmacy - Shufyani, Fahma; Siregar , Syati Manaharawan; Yulia , Rahma (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Introduction: Hypertension is one of the most dangerous health problems in the world, because hypertension is the main risk factor that leads to cardiovascular disease such as heart attack, heart failure, stroke and kidney disease. The aim of this study was to determine the relationship between level of knowledge and adherence to taking medication in hypertensive patients at the Medan Central Care Pharmacy.. This Method This research method uses quantitative descriptive analytical methods using a cross-sectional design. The sampling technique uses purposive sampling technique. Data were analyzed using the Chi Square test. Data collection was carried out in June 2023. The research population was hypertension sufferers at the Medan Central Care Pharmacy. The sample for this research was 97 respondent. The results of this study showed that the frequency distribution of high knowledge was 45 respondents (46.4%), medium was 36 respondents (37.1%) and low was 16 respondents (16.5%). The frequency distribution of medication adherence was 19 respondents (19.6%) high, 45 respondents (46.4%) medium and 33 respondents (34%) low. The results of the chi-square test of knowledge with medication adherence showed a p-value of 0.000<0.05. The conclusion in this study is that the respondent's level of knowledge about hypertension is in the high category, the respondent's level of medication adherence is in the medium category and there is a relationship between the level of knowledge and medication adherence in hypertension patients at the Medan Central Care Pharmacy.